Understanding Gen Z’s Investment Intentions in the Sharia Capital Market: The Role of Religiosity, Religious Events, Attitude, Behavioral Control and Profit Maximization - Afifah; Tubastuvi, Naelati (Jurnal Ilmu Manajemen, 2025)
This study aims to examine the influence of religiosity, religious events, attitude, perceived behavioral control, and profit maximization orientation on Generation Z’s investment intention toward Sharia products in the capital market. The research involved 230 respondents residing in Central Java (Indonesia) and employed a quantitative approach with data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that religious events, attitude, and profit maximization have a significant positive influence on investment intention, while religiosity and perceived behavioral control do not show significant effects. In making investment decisions within the Sharia capital market, Generation Z tends to consider religious events as important moments, along with the potential financial returns they may gain. Additionally, their attitudes, shaped by Islamic values, also contribute to strengthening their interest in investing in instruments that align with Sharia principles.